2003
DOI: 10.1046/j.1537-2995.2003.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Seven‐day storage of apheresis platelets: report of an in vitro study

Abstract: Although a continuing decline of platelet in vitro characteristics can be observed for storage beyond 5 days, apheresis platelets in plasma stored 100 to 400 mL per bag, 1.0 x 10(6) to 2.5 x 10(6) platelets per microL, and a maximum of 5.1 x 10(11) platelets per bag maintained in vitro platelet characteristics over 7 days of storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
49
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 29 publications
11
49
1
Order By: Relevance
“…Thirdly, in order to mimic the proper clinical setting, we first used increasing amounts of blood-banked platelet concentrates in order to evaluate platelet recovery. However, in accordance with previously published reports, we observed an important decrease in platelet aggregation ability during the storage time in the platelet concentrate form [39] mainly as a result of metabolic changes in platelets maintained in that medium [40] which prevented us from continuing with this approach. However, it has recently been published that decreased platelet aggregation in stored platelet concentrate improves in the body after transfusion, and transfused platelets have similar aggregation ability compared with the platelets derived from the patient [41], so we used a pool of platelets donated directly from five healthy volunteers.…”
Section: Discussionsupporting
confidence: 92%
“…Thirdly, in order to mimic the proper clinical setting, we first used increasing amounts of blood-banked platelet concentrates in order to evaluate platelet recovery. However, in accordance with previously published reports, we observed an important decrease in platelet aggregation ability during the storage time in the platelet concentrate form [39] mainly as a result of metabolic changes in platelets maintained in that medium [40] which prevented us from continuing with this approach. However, it has recently been published that decreased platelet aggregation in stored platelet concentrate improves in the body after transfusion, and transfused platelets have similar aggregation ability compared with the platelets derived from the patient [41], so we used a pool of platelets donated directly from five healthy volunteers.…”
Section: Discussionsupporting
confidence: 92%
“…If this observation is due to the technique of cell separation needs further investigation. A previous in vitro study has found impaired function of PC after a storage time exceeding 7 days [32]. Additionally, Schrezenmeier et al mentioned in a recent review article, that several factors might influence the quality of PC such as extent of cell separation (residual leukocytes), plasma content or additive solution which in turn might affect also lipid concentration of PC [33].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD62P on day 0 averaged 1094.7 percent after activation with TRAP-6 and it dropped to 547.3 percent on day 5 after activation with TRAP-6, as compared with the control values. CD62P expression at the platelet surface is one of the most common markers of platelet activation in PCs and there were standardized protocols established to compare the activation of platelets during storage with increased CD62P level over time (37,(278)(279)(280) In the present study, this criterion was fixed as a gold standard for the evaluation of PL-EV levels as a quality control approach.…”
Section: Discussionmentioning
confidence: 99%